Empirical Essays in Natural Resources, Commodity Prices, and Applied Macroeconomics - Davarzani, Farzaneh (Université d'Ottawa / University of Ottawa, 2022)
This thesis presents three distinct chapters that look at different challenges faced by advanced and emerging market economies. Given the issues explored in these chapters, I contribute to several strands of economic literature. Yet, each chapter is motivated by its policy relevance and is embedded in the issues advanced and emerging market countries face. Chapter 1 explores the impact of income inequality on domestic investment in resource-rich countries. Income inequality may affect investment through different mechanisms. For instance, it could distort incentives for domestic investment; high-income inequality may discourage investment in public goods since low-income non-investors may benefit more from the returns on investment. As a result, countries with higher income inequality are expected to contribute less to their domestic investment. To investigate the relationship between income inequality and domestic investment, I use the data for 57 resource-rich countries from 1982-2015. Due to endogenous relationships among variables, I use generalized method-of moments estimators that employ lagged regressors as instruments in the estimation. Using a variety of income inequality measures, I find a negative and significant relationship between these two economic indicators: income inequality and domestic investment. This result could help resource-rich countries achieve higher growth from their resource endowments. The second chapter studies the extent to which worldwide shocks can explain country-specific inflation fluctuations. My benchmark model proxy world shocks with shocks to commodity prices. First, using a factor model of commodity prices, I extract three leading factors characterizing their co-movement. Then, I use the commodity price factors in a structural vector autoregressive model to investigate the fraction of inflation fluctuations that commodity price shocks can explain. My estimation is based on the data for 67 advanced and emerging market economies from 1970-2014. Furthermore, I examine the impact of world shocks on inflation through additional mechanisms, such as changes in the world interest rate and the global economic activity index. Compared to the previous literature, I find the increased importance of world shocks in explaining country-specific inflation fluctuations. This result can guide policymakers in setting the relevant monetary policy to control or prevent inflationary pressures in an economy. Finally, the third chapter studies whether commodity price shocks matter for estimating the output gap. First, I apply the Beveridge and Nelson decomposition method and calculate the share explained by world shocks in the variance decomposition of the output gap. In my analysis, world shocks affect the output gap through commodity price indices and global economic factors. My study includes five advanced and ten emerging market economies from 1980-2018. Then, I investigate whether commodity price shocks can improve the accuracy of this estimation. To do this, I exclude commodity price indices from my model to estimate the output gap. Finally, I use output gaps estimated with and without commodity price indices in an inflation forecasting model to compare the forecast errors of predicted inflation. Using a forecast error test, I find that the estimated output gap using commodity price indices would provide better results in forecasting inflation than other output measures.
Keywords: Commodity Prices; Natural Resources; Macroeconomic Indicators